2024
DOI: 10.1287/orsc.2021.15814
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Negative Attention: Status and Costs in the Market for Audit Services

Amandine Ody-Brasier,
Amanda J. Sharkey

Abstract: Prior work has emphasized the role of positive attention spillovers in driving cost advantages for high-status firms, with exchange partners offering preferential terms to high-status organizations because they anticipate benefits. Yet, spillovers from a client to a supplier may also be negative. These negative spillovers can be exacerbated when high-status actors are involved, because of the high level of publicity they attract. In this paper, we propose that suppliers’ concerns about negative attention are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Our study echoes the literature on the information mechanism of media attention (Guest, 2021;Jiang et al, 2022;Ody-Brasier & Sharkey, 2023). As an information intermediary, the media can directly and indirectly disseminate information about ESG rating divergence.…”
Section: The Role Of Mediasupporting
confidence: 79%
“…Our study echoes the literature on the information mechanism of media attention (Guest, 2021;Jiang et al, 2022;Ody-Brasier & Sharkey, 2023). As an information intermediary, the media can directly and indirectly disseminate information about ESG rating divergence.…”
Section: The Role Of Mediasupporting
confidence: 79%
“…• Motivate low-status actors' redirection to domains not attended by high-status actors (e.g., Reschke, Azoulay, & Stuart, 2018) • Prompt associates of high-status actors to adopt precautionary measures to hedge against negative spillover (e.g., Ody-Brasier & Sharkey, 2023) iii. Magnet:…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that associates of high-status actors often engage in preempting behavior when they fear that they might be indirectly held accountable for these actors’ transgressions. Ody-Brasier and Sharkey (2023) observe that high-status firms, when faced with allegations or proven instances of misconduct, not only draw scrutiny to themselves but also place their service providers into the spotlight, potentially undermining the latter’s status. As a precautionary measure to hedge against this risk, these service providers, particularly accounting firms entrusted to certify balance sheets, levy higher fees on high-status firms.…”
Section: Prestige (Merit-based) Statusmentioning
confidence: 99%